Engineering nanoparticles (ENPs) in aquatic environments and soil-plant ecosystems: transformation, toxicity, and environmental challenges - Islam, A. K. M. Nazrul; Uddin, Md. Nizam; Ridwan, Asib; Neon, Asif Karim; Rab, Md. Fozle (Frontiers in Soil Science, 2025)
The ever-increasing use of diverse types of engineered nanoparticles (ENPs) in industries, medicine, and consumer products has resulted in their uncontrolled release into aquatic environments and soil-plant systems. ENPs may transform and release toxic by-products upon release, raising concerns about their environmental behavior and potential risks. However, accurately measuring the concentrations of ENP in these ecosystems remains challenging. Recent studies have highlighted the toxic effects of ENPs on various organisms, but assessing the risk in aquatic and soil-plant systems consists of a critical issue in nanoecotoxicology. ENPs interact with various environmental materials like organic matter, soil, sludge, and other pollutants. These interactions of ENPs can form complex assemblies, which may alter the toxicity and environmental fate. This study examines the interactions of ENPs in aquatic and soil-plant environments, focusing on their transformation, toxicity, and ecological impact. Identification of the knowledge gaps related to the ENP interaction and outlining the directions for future consideration for a better understanding of the environmental risks have been explained in this study. Additionally, the research addresses the challenges of evaluating nanotoxicity and highlights the need for improved environmental regulations and assessment techniques for engineered nanomaterials.